New evidence on the sequence of deglacial warming in the tropical Indian Ocean - Naidu, P.D.; Govil, P. (John Wiley, 2010)
The transition from the Last Glacial Maximum to the Holocene was an internal of climate variability that was characterised by large spatial and temporal variations. Here we show that deglaciation warming in the northern Indian Ocean was initiated ca. 19 ka, which is contemporary with deglaciation warming in the Antarctica and Southern Ocean. A gradual warming occurred during the glacial/Holocene transition in the northern Indian Ocean, unlike the two-step warming seen in Greenland and the North Atlantic. Synchronous deglacial warming ca. 19 ka in Antarctica and the northern Indian Ocean suggests a strong connection in the propagation of climate signals between Antarctica and the Indian Ocean, probably through the Indonesian Throughflow and/or Subantarctic Mode Water